STUDY OF THE REVEALED OBJECT OF THE CULTURAL HERITAGE "PETER'S THE GREAT LODGE" IN DERBENT - Gadziev, M S; Abiev, A K; Budajciev, A L; Abdullaev, A M; Sausev, K B (History, Archeology and Ethnography of the Caucasus, 2015)
The article presents the review of archaeological researches on the revealed cultural heritage object “Peter’s the Great Lodge” in Derbent. As a result of the carried-out works the remains of a dugout in which the Emperor Peter I stopped on lodging for the night on August 23, 1722 during thePersian campaign were revealed.The drawings and the photos of the 19th – the beginning of the 20th century representing Peter’s dugout and the columned building built over it in the 1870s' are considered in article.
Keywords: Derbent; Peter the Great; Persian campaign of 1722